Degree of Horizontal Integration of Life Skills in Second Basic Grade Curriculum in Jordan - Elhaj Qasem, Hadeel Nabil; Abu Sneineh, Odeh (Journal of Educational and Psychological Sciences, 2019)
The study aimed to reveal the degree of horizontal integration in life skills in the second grade curriculum in Jordan. To achieve the objective of the study، the researcher used the analytical descriptive method.The study sample included the Arabic and Islamic education books and social and national education. The results of the study indicated that manual in its first and second section. The life skills to be included in the sample study books included (51) skills divided into five basic skills: creative thinking skills، problem solving، the communication، dealing with others، decision making. Results also included a harezontal integration in the skills of life between the Arabic language and Islamic educationby (38.3%) ، which is high according to the criterion of the study. There is also a horizontal integration in life skills between the Arabic language book and the social and national education guide by (37.7%)، High percentage، and finally the existence of horizontal integration is very weak in the skills of life between the book of Islamic based on education and the huide of social and national education by (24%). The study came out with several recommendation، the most important of which are: Enrichment of the curriculum on the subject of life skills، and their inclusion in an integrative manner baser on a standard of integration developed by the directorate of curriculum. And taking into account problem solving skills during the construction and design of the curriculum.
Keywords: degree; horizontal integration; life skills; second grade curricula